## B3: thực hiện phép tính: a) – $\frac{3}{4}$ – $\frac{2}{7}$ b) 5/24 – $\frac{-4}{32}$ c) 8-9/2 d) 2/3- $\frac{-3}{4}$ e) 7/36 – 24/-27 – 12/18 f)

Question

B3: thực hiện phép tính:
a) – $\frac{3}{4}$ – $\frac{2}{7}$
b) 5/24 – $\frac{-4}{32}$
c) 8-9/2
d) 2/3- $\frac{-3}{4}$
e) 7/36 – 24/-27 – 12/18
f) – 3/13 + 7/12 – 10/13 + 5/12
g) -2/5 : 11/6
h) (-2) : 11/6
i) -14/13 : 7
k) 4/9 + 4/3 . 18/4
n) 6/13 . 5/7 + 6/13 . 2/7 + 7/13

in progress 0
1 năm 2021-08-30T21:15:18+00:00 2 Answers 8 views 0

1. Đáp án:

a) -$\frac{3}{4}$ – $\frac{2}{7}$

= $\frac{-3}{4}$ + $\frac{2}{7}$

= $\frac{-21}{28}$ + $\frac{8}{28}$

= $\frac{-13}{28}$

b) $\frac{5}{24}$ – $\frac{-4}{32}$

= $\frac{5}{24}$ + $\frac{1}{8}$

= $\frac{5}{24}$ + $\frac{3}{24}$

= $\frac{1}{3}$

c) 8 – $\frac{9}{2}$

= $\frac{8}{1}$ + $\frac{-9}{2}$

= $\frac{16}{2}$ + $\frac{-9}{2}$

= $\frac{7}{2}$

d) $\frac{2}{3}$ – $\frac{-3}{4}$

= $\frac{2}{3}$ + $\frac{3}{4}$

= $\frac{8}{12}$ + $\frac{9}{12}$

= $\frac{17}{12}$

e) $\frac{7}{36}$ – $\frac{24}{-27}$ – $\frac{12}{18}$

= $\frac{7}{36}$ + $\frac{24}{27}$ + $\frac{-12}{18}$

= $\frac{7}{36}$ + $\frac{8}{9}$ + $\frac{-2}{3}$

= $\frac{7}{36}$ + $\frac{32}{36}$ + $\frac{-24}{36}$

= $\frac{5}{12}$

f) $\frac{-3}{13}$ + $\frac{7}{12}$ – $\frac{10}{13}$ + $\frac{5}{12}$

= $\frac{-3}{13}$ + $\frac{7}{12}$ + $\frac{-10}{13}$ + $\frac{5}{12}$

= ($\frac{-3}{13}$ + $\frac{-10}{13}$) + ($\frac{7}{12}$ + $\frac{5}{12}$)

= -1 + 1

= 0

g) $\frac{-2}{5}$ : $\frac{11}{6}$

= $\frac{-2}{5}$ . $\frac{6}{11}$

= $\frac{-12}{55}$

h) (-2) : $\frac{11}{6}$

= $\frac{-2}{1}$ . $\frac{6}{11}$

= $\frac{-12}{11}$

i) $\frac{-14}{13}$ : 7

= $\frac{-14}{13}$ .  $\frac{1}{7}$

= $\frac{-2}{13}$

k) $\frac{4}{9}$ + $\frac{4}{3}$ . $\frac{18}{4}$

= $\frac{4}{9}$ + 6

= $\frac{4}{9}$ + $\frac{6}{1}$

= $\frac{4}{9}$ + $\frac{54}{9}$

= $\frac{58}{9}$

n) $\frac{6}{13}$ . $\frac{5}{7}$ + $\frac{6}{13}$ . $\frac{2}{7}$ + $\frac{7}{13}$

= $\frac{6}{13}$ . ($\frac{5}{7}$ + $\frac{2}{7}$) + $\frac{7}{13}$

= $\frac{6}{13}$ . 1 + $\frac{7}{13}$

= $\frac{6}{13}$ + $\frac{7}{13}$

= 1

2. $a) -\dfrac{3}{4}-\dfrac{2}{7}\\=-\dfrac{21+8}{28}\\=-\dfrac{29}{28}\\b) \dfrac{5}{24}-\dfrac{-4}{32}\\=\dfrac{5}{24}+\dfrac{4}{32}\\=\dfrac{5}{24}+\dfrac{1}{8}\\=\dfrac{5+3}{24}\\=\dfrac{8}{24}=\dfrac{1}{3}\\c) 8-\dfrac{9}{2}\\=\dfrac{16-9}{2}\\=\dfrac{7}{2}\\d) \dfrac{2}{3}-\dfrac{-3}{4}\\=\dfrac{2}{3}+\dfrac{3}{4}\\=\dfrac{8+9}{12}\\=\dfrac{17}{12}\\e) \dfrac{7}{36}-\dfrac{24}{-27}-\dfrac{12}{18}\\=\dfrac{7}{36}+\dfrac{24}{27}-\dfrac{2}{3}\\=\dfrac{7}{36}+\dfrac{8}{9}-\dfrac{2}{3}\\=\dfrac{7+32-24}{36}\\=\dfrac{15}{36}=\dfrac{5}{12}\\f) -\dfrac{3}{13}+\dfrac{7}{12}-\dfrac{10}{13}+\dfrac{5}{12}\\=\dfrac{-3-10}{13}+\dfrac{7+5}{12}\\=\dfrac{-13}{13}+\dfrac{12}{12}\\=-1+1=0\\g)-\dfrac{2}{5}:\frac{11}{6}\\=-\dfrac{2}{5}.\dfrac{6}{11}\\=-\dfrac{12}{55}\\h)(-2):\dfrac{11}{6}\\=-2.\dfrac{6}{11}\\=-\dfrac{12}{11}\\i)-\dfrac{14}{13}:7\\=-\dfrac{14}{13}.\dfrac{1}{7}\\=-\dfrac{2}{13}\\k) \dfrac{4}{9}+\dfrac{4}{3}.\dfrac{18}{4}\\=\dfrac{4}{9}+6\\=\dfrac{58}{9}\\n) \dfrac{6}{13}.\dfrac{5}{7}+\dfrac{6}{13}.\dfrac{2}{7}+\dfrac{7}{13}\\=\dfrac{30}{91}+\dfrac{12}{91}+\dfrac{7}{13}=1$